(untitled) (Journal of Engineering Science, 2025)
Tropical cyclones (TCs) are the most destructive atmospheric phenomena regarding damage to lives and properties over the coastal regions. An attempt has been made to examine the vertical structure of two TCs (Amphan and Bulbul) formed over the Bay of Bengal (BoB) with unlike intensities. Weather Research and Forecasting (WRF) model is deployed to simulate the selected TCs. The model is configured with two two-way interactive nested domains with a horizontal resolution of 27 km and 9 km. Outputs from the 9 km domain are considered for analysis. The vertical structure of different parameters like tangential and radial wind, relative humidity, vorticity, vertical velocity, etc. are examined. WRF model is capable enough to simulate the vertical structure of different parameters. It was found that Amphan’s structure is simulated realistically better as compared to Bulbul. Investigation of the vertical structure of TCs would enhance the knowledge in understanding the role of vertical structure in predicting TCs intensity as well as movement. Journal of Engineering Science 15(2), 2024, 41-50